1998
DOI: 10.1002/(sici)1097-0045(19980101)34:1<23::aid-pros3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of digital rectal massage on urinary prostate-specific antigen: Interest for the detection of local recurrence after radical prostatectomy

Abstract: BACKGROUND Following radical prostatectomy, urinary prostate‐specific antigen (uPSA) may originate from periurethral glands or from recurrent carcinomatous prostatic cells. We evaluated massage of the urethro‐vesical anastomosis as a uPSA‐releasing method for the detection of local recurrence. METHODS PSA was assessed (PSA IMx™, Abbott Diagnostic, Rungis, France) in serum and in the first voided urine before and after massage in 59 patients: 7 after cystoprostatectomy for bladder cancer, 22 with prostate in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…Over the years, PSA has been measured on different samples: in urine voided before and after prostate massage, 3,4 in first-voided urine, [4][5][6] in single midstream sample of urine [7][8][9][10] and in 24-hour urine specimens. [11][12][13] The fact that a urine specimen contains more PSA certainly appears to be an advantageous issue in terms of method of choice for PSA measurement.…”
mentioning
confidence: 99%
“…Over the years, PSA has been measured on different samples: in urine voided before and after prostate massage, 3,4 in first-voided urine, [4][5][6] in single midstream sample of urine [7][8][9][10] and in 24-hour urine specimens. [11][12][13] The fact that a urine specimen contains more PSA certainly appears to be an advantageous issue in terms of method of choice for PSA measurement.…”
mentioning
confidence: 99%
“…Algunos grupos intentaron evaluar, sin éxito, si la medición del PSA en orina podría ayudar al diagnóstico de una recidiva local 27 . Probablemente el fracaso de dichos trabajos residía en que el epitelio de las glándulas paruretrales también sintetiza esta proteína 28 .…”
Section: Resultados Y Discusiónunclassified
“…Probablemente el fracaso de dichos trabajos residía en que el epitelio de las glándulas paruretrales también sintetiza esta proteína 28 . Posteriormente se planteo la posibilidad de medir el PSA total y la fracción libre del PSA en orina antes y tras el masaje de la anastomosis 27 . Los primeros resultados parecían prometedores, la medición de la fracción libre de PSA en el chorro miccional medio permitiría distinguir una recidiva tumoral local de una recidiva hiperplásica.…”
Section: Resultados Y Discusiónunclassified
“…Therefore, it is necessary to identify and remove proteins that are from the urinary system among proteins found in urine, in order to identify biomarkers for diseases in distal organs [3]. Currently, the most useful disease markers in urine have been largely for urogenital diseases, such as urothelial cancer [4], renal cell carcinoma [5], prostate cancer [6], and bladder cancer [7]. A few recent studies have demonstrated the feasibility in using urinary proteins as disease markers in distal organs, such as ovarian carcinoma [8], lung cancer [9], hepatocellular carcinoma [10], and gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%